The Effect of Ruqyah Syar’iyyah Therapy on Anxiety, Stress and Depression Among Health Science Students - Yusuf Waliyyun Arifuddin; Akhmad Yanuar Fahmi (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2018)
Backgroud: University student is one of the community groups that are vulnerable to mental health problems. Loads of course are likely to be high, demanding students must meet the target that has been charged by the university. Especially, the faculty or department does require the seriousness and the achievement of learning objectives in a timely manner, for example the faculty of medicine, nursing, midwifery and others. Therefore, students have a high propensity to suffer anxiety disorder, stress and depression. Many ways have been made to reduce these anxiety, stress and depression. Among of them are ruqyah syar’iyyah (incantation) is alternatively offered as the Islamic treatment. The initial phase of this therapy is problems diagnose (or counselling as known in psychology). The second phase is tauziyah (advice) with materials that are relevant to the problem (or problem solving if termed in psychology). The third phase is listening to the verses of Al-Qur’an and or be coincided with taking prophet medicines such as honey, black seed oil, zam - zam water, olive oil, and sidr leaves.Purpose: The purpose of this study was to determine whether the therapy of ruqyah syar'iyyah effects in reducing the levels of anxiety disorders, stress and depression among health science students.Method: The research method used is a quasi-experimental pre-post test design with a total sample of 54 respondents that refer to the scale DASS 42 (Depression Anxiety and Stress Scale). Sampling was done with a purposive sampling. Each of the mentioned disorders was 18 samples (9 treated samples and 9 untreated samples).Results: Based on the statistical test method of Wilcoxon Signed Ranks Test with its significance level α (0.05), it can be concluded that there is a significant effect of ruqyah syar'iyyah treatment in decreasing the levels of anxiety, stress and depression among health students.Conclussion: For further research, it is high recommended to examine respondents with controlled disorders as in a mental hospital, or rehabilitation places that service for anxiety disorders, stress and depression.